Implementasi Civic Dispotition Mata Pelajaran Pendidikan Pancasila dalam Meningkatkan Kecintaan Tanah Air pada Peserta Didik Kelas 2 di Sekolah Dasar - Maheswari, Nada Kencana; Fatayan, Arum (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the implementation of civic disposition in Pancasila Education to foster love for the homeland among 2nd-grade students at SDN Dukuh 08 Pagi. The urgency of this research lies in the increasing need to strengthen national character and patriotism from an early age, especially in the face of various contemporary challenges that may erode these values. This research employs a qualitative descriptive method, utilizing observations, interviews with school principals, teachers, students, and parents, as well as documentation to collect data. The findings indicate that the school actively implements civic disposition through various learning methods and extracurricular activities, which significantly contribute to enhancing students' love for their homeland and their understanding of Pancasila values. Challenges identified include limited teaching staff and digital literacy. However, the school employs strategies such as varied teaching methods and increased student appreciation to overcome these obstacles. The study concludes that the comprehensive implementation of civic disposition in Pancasila Education effectively promotes patriotism and positive behavioral changes in students.